2019
DOI: 10.1136/bmjopen-2019-034485
|View full text |Cite
|
Sign up to set email alerts
|

Health-related preferences of older patients with multimorbidity: an evidence map

Abstract: ObjectivesTo systematically identify knowledge clusters and research gaps in the health-related preferences of older patients with multimorbidity by mapping current evidence.DesignEvidence map (systematic review variant).Data sourcesMEDLINE, EMBASE, PsycINFO, PSYNDEX, CINAHL and Science Citation Index/Social Science Citation Index/-Expanded from inception to April 2018.Study selectionStudies reporting primary research on health-related preferences of older patients (mean age ≥60 years) with multimorbidity (≥2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 176 publications
(231 reference statements)
0
17
0
Order By: Relevance
“…To provide decision support to health professionals and help this complex patient population in an emotionally difficult situation, we systematically reviewed EoL care preferences in older patients with multimorbidity. We based the review on a knowledge cluster of EoL care preferences that we previously identified for an evidence map we developed on health-related preferences in older patients with multimorbidity [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…To provide decision support to health professionals and help this complex patient population in an emotionally difficult situation, we systematically reviewed EoL care preferences in older patients with multimorbidity. We based the review on a knowledge cluster of EoL care preferences that we previously identified for an evidence map we developed on health-related preferences in older patients with multimorbidity [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“… 8 A recent review found that top health-related patient preferences of older patients with multimorbidity are health outcome prioritisation and goal setting and self-management. 9 In recent years, self-management tools have been acknowledged as an effective way to optimise disease management because persons can ‘function on their own behalf in health promotion, disease prevention and management’. 10 11 Self-management tools also have the potential to alleviate time and resource burdens on primary care healthcare professionals (eg, physicians, nurses, dietitians and pharmacists) who most often are left to address all aspects of disease management (ie, risk assessment, diagnosis and treatment).…”
Section: Introductionmentioning
confidence: 99%
“…1 We argue that a more holistic approach for the care of elderly, chronically ill patients is needed which considers three aspects strongly linked to self-efficacy: patients' spiritual needs, social activity and self-care, i.e., patients' activeness in areas that can enhance well-being other than taking medication. [2][3][4] Studies show that patients have voiced the wish for holistic attention from their physician, 5,6 while many GPs acknowledge that meeting these needs should be an integral part of primary care. 4,[7][8][9] At the same time, patients and GPs alike report a lack in competencies on the part of the physician in terms of providing holistic primary care, in particular in meeting patients' spiritual needs.…”
Section: Introductionmentioning
confidence: 99%